EVALUASI KONDISI SAHAM MELALUI ANALISIS FUNDAMENTAL DENGAN METODE DIVIDEND DISCOUNT MODEL (DDM) TERHADAP KEPUTUSAN INVESTASI PADA PERUSAHAAN SUB SEKTOR PULP AND PAPER YANG TERDAFTAR DI BEI PERIODE 2011-2015 - Astria Semaradilla Syari (Jurnal Ekonomi STIEP, 2018)
The purpose of this study was to: (1) determine the condition of stocks through fundamental analysis by the DDM on the company's pulp and paper subsectors period 2011-2015; (2) determine the company's investment decisions pulp and paper subsectors period 2011-2015. The results of this study indicate that (1) the highest intrinsic value is at PT Fajar Surya Wisesa Tbk which is equal to 924.7226 and the lowest intrinsic value is at Paper Factory PT Tjiwi Kimia Tbk, which amounted -1,787,541; (2) The company PT kedawung Setia Industrial Tbk in the period 2011-2015 has a condition undervalued stocks. Meanwhile, other companies namely PT Alkindo Naratama Tbk, PT Fajar Surya Wisesa Tbk, PT Indah Kiat Pulp & Paper Tbk, PT Suparma Tbk, and PT Pabrik Kertas Tjiwi Kimia Tbk experienced overvalued.